تحديات تمويل الحكومة الالكترونية: مفاهيم و اليات - د. سرمد كوكب الجميل (PROSPECTIVE RESEARCHES, 2023)
The present paper deals with the concept of the electronic government which has been adopted by many countries to improve the public service provided by the government. It also tackles the foundations and their limitations as well applied samples as programmes performed by the ministries of the government. Accordingly, the E.G. is but a project which can be estimated and performed in connection to the finance provided by the government. The research analyzes the details with reference to governmental applications in some countries through introducing the budget and the financial mechanism. The research has concluded that financing the E.G. project is connected to cost-benefit evaluation to be put on the scale of priorities which differs from one state to another according to financial situation and the mechanism of performance.